Adaptive evolution in the Saccharomyces kudriavzevii Aro4p promoted a reduced production of higher alcohols. Issue 12 (28th October 2022) - Tapia, Sebastián M.; Pérez‐Torrado, Roberto; Adam, Ana Cristina; Macías, Laura G.; Barrio, Eladio; Querol, Amparo
Abstract: The use of unconventional yeast species in human‐driven fermentations has attracted a lot of attention in the last few years. This tool allows the alcoholic beverage industries to solve problems related to climate change or the consumer demand for newer high‐quality products. In this sense, one of the most attractive species is Saccharomyces kudriavzevii, which shows interesting fermentative traits such as the increased and diverse aroma compound production in wines. Specifically, it has been observed that different isolates of this species can produce higher amounts of higher alcohols such as phenylethanol compared with Saccharomyces cerevisiae . In this work, we have shed light on this feature relating it to the S. kudriavzevii aromatic amino acid anabolic pathway in which the enzyme Aro4p plays an essential role. Unexpectedly, we observed that the presence of the S. kudriavzevii ARO4 variant reduces phenylethanol production compared with the S. cerevisiae ARO4 allele. Our experiments suggest that this can be explained by increased feedback inhibition, which might be a consequence of the changes detected in the Aro4p amino end such as L26 Q24 that have been under positive selection in the S. kudriavzevii specie. Abstract : Strains carrying the Saccharomyces kudriavzevii ARO4 allele reduce the phenylethanol and tyrosol production compared with the strains expressing the S. cerevisiae allele. The S. kudriavzevii Aro4p is more sensitive to the tyrosine inhibition.